2019
DOI: 10.1186/s13104-019-4549-9
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual syndrome and factors associated with it among secondary and preparatory school students in Debremarkos town, North-west Ethiopia, 2016

Abstract: Objective The purpose of this study was to assess the magnitude of premenstrual syndrome and its associated factors among secondary school students in Debremarkos, North west Ethiopia. Results Premenstrual syndrome was reported by 81.3% of the participants. Statistically significant association was observed between the occurrence of PMS and age, AOR (CI) 1.20 (1.01, 1.44), involving in heavy non-academic duties, AOR 95% (CI)  2.13 (1.17, 3.89), early menarche (< 12 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
3
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 12 publications
5
39
3
6
Order By: Relevance
“…The objective of this research was to find out the association between PMS/PMDD with various factors such as socio-demographic, dietary and lifestyle. In this study, the average age of study respondents was 20.41 (17.93-22.89) years, which was comparable with the studies done in Ethiopia[ 1 ] (17.61 ± 1.93 years), Bhavnagar, India[ 18 ] (18.9 ± 1.6 years), Iran[ 2 ] (16.0 ± 2.3 years), Turkey[ 19 ] (19.5 ± 1.3 years) and UAE[ 12 ] (20.07 ± 1.53 years) as far recruiting young adults in the study is concerned. The urban to rural difference was vast in the present study, which depends on the locality of the institute as well as the admission criteria for the medical courses.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The objective of this research was to find out the association between PMS/PMDD with various factors such as socio-demographic, dietary and lifestyle. In this study, the average age of study respondents was 20.41 (17.93-22.89) years, which was comparable with the studies done in Ethiopia[ 1 ] (17.61 ± 1.93 years), Bhavnagar, India[ 18 ] (18.9 ± 1.6 years), Iran[ 2 ] (16.0 ± 2.3 years), Turkey[ 19 ] (19.5 ± 1.3 years) and UAE[ 12 ] (20.07 ± 1.53 years) as far recruiting young adults in the study is concerned. The urban to rural difference was vast in the present study, which depends on the locality of the institute as well as the admission criteria for the medical courses.…”
Section: Discussionsupporting
confidence: 86%
“…Premenstrual syndrome (PMS) is the term coined for a variety of symptoms occurring in the luteal phase of the menstrual cycle which resolves in some days of onset of menstrual blood flow. [ 1 ] Although the symptoms are of physical as well as psychological in nature, it is essentially a neuro-endocrine disorder with biological, social and psychological parameters. [ 2 ] It has been observed that more than 90% of the women throughout the world experience its symptoms which include, but not limited to, features like anxiety, irritability, headache, fatigue, breast tenderness, social withdrawal, change in mood, sleep disruption and depression.…”
Section: Introductionmentioning
confidence: 99%
“…shows a statistically insignificant association between PMS and menstrual patterns [7]. The pooled odds ratio also shows a statistically insignificant association between menstrual pattern and PMS (OR: 3.19, 95% CI: 0.94,10.80) (Fig 4).…”
Section: Plos Onementioning
confidence: 86%
“…All studies included in this analysis were conducted using a cross-sectional study design [7,8,[16][17][18][19][20][21][22]. For eight of these studies, the premenstrual syndrome scoring tool of Diagnostic and Statistical Manual of Mental Disorders, 4th Ed (DMS IV) was used while the American College of Obstetricians and Gynecologists (ACOG) was used for the remaining one study [7]. All the included studies were done from 2002 to 2019 and their sample size ranged from 181 [19] to 667 [17].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation